A Simulated Annealing Approach to Solve Fuzzy Multi-Objective Linear Model for Supplier Selection in a Supply Chain - Parthiban, P; Dominic P, Dhanapal Durai; dhanalakshmi, p (2010)
Abstract—Suppliers play a key role in achieving the objective of supply chain. Hence selecting the right suppliers and their quota allocation is a very important in achieving corporate competition. Supplier selection is a multiple criteria decision-making (MCDM) problem which is affected by several factors. At the same time due to the presence of vague and imprecise input parameters, makes the supplier selection complicated. During this project a fuzzy Multi-objective linear model is developed to achieve three important goals: Cost minimization, Quality maximization and Service level maximization and further it is converted into crisp single objective programming model using membership functions of the three objectives. Finally the problem is solved by using simulated annealing algorithm to enable the decision-maker to select the right suppliers and allocate their quota in order to minimize the cost, maximize the quality level and again maximize the service level.